1998
DOI: 10.1176/ajp.155.4.543
|View full text |Cite
|
Sign up to set email alerts
|

Reduction by Paroxetine of Suicidal Behavior in Patients With Repeated Suicide Attempts But Not Major Depression

Abstract: This study indicates that enhancing serotonergic function with an SSRI may reduce suicidal behavior in a subgroup of patients who have attempted suicide more than once but who do not suffer from major depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(73 citation statements)
references
References 24 publications
1
71
0
1
Order By: Relevance
“…For example, Verkes et al found a significant decrease in suicide attempts in patients without major depression who were treated with paroxetine. 41 These findings, along with our results, suggest that screening and subsequently treating targeted males for depressive symptoms may decrease their aggressive behavior.…”
Section: Discussionsupporting
confidence: 71%
“…For example, Verkes et al found a significant decrease in suicide attempts in patients without major depression who were treated with paroxetine. 41 These findings, along with our results, suggest that screening and subsequently treating targeted males for depressive symptoms may decrease their aggressive behavior.…”
Section: Discussionsupporting
confidence: 71%
“…On the one hand, psychosocial interventions that are successful in treating depression and hopelessness among suicidal individuals have shown minimal efficacy in reducing rates of attempted suicide (Lerner and Clum, 1990;Rotheram-Borus et al, 1996). On the other hand, interventions that reduce the frequency and severity of attempted suicide in adult samples generally are not effective in ameliorating depressive affect (Linehan et al, 1991;Verkes et al, 1998). Together, these findings suggest that the change mechanisms required for the reduction of suicidal behavior might differ from those of treating depression, and that one cannot assume that suicidal risk decreases in tandem with depressive affect.…”
Section: Discussionmentioning
confidence: 97%
“…Several recent controlled trials have reported that specific serotonin reuptake inhibitors (SSRI) are effective at reducing the recurrence of suicide attempts and decreasing impulsive aggression traits in subjects with and without personality disorders. 12,13 These main effects were independent of an antidepressant effect.…”
mentioning
confidence: 82%